2016
DOI: 10.1111/rda.12712
|View full text |Cite
|
Sign up to set email alerts
|

Buffalo (Bubalus bubali) Late Embryo and Foetus Development: A Morphological Analysis

Abstract: Many researches describe the embryonic developmental features in domestic animals; however, in farm animals, they are scarce. Most farm animal studies are related to assisted reproduction and embryos transfer techniques. But, morphological features and size measure to estimate the age gestation are rarely reported in literature. Thus, in this study, we described the developmental changes in the bubaline (Bubalus bubali) concepts from 21 to 60 days of gestation. Our results revealed that buffalo embryos similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the present study the digestive tube was first observed on the 23rd day as in sheep, buffalo and equine feti at 25th day of gestation (Morini et al, 2016;Rodrigues et al, 2014;Trahair & Robinson, 1986), respectively. The primitive intestine was covered by mesenchymal mass on the 23rd day similarly to equine feti at 25th day of gestation (Franciollia et al, 2011).…”
Section: Histogenesis Of Intestinementioning
confidence: 52%
“…In the present study the digestive tube was first observed on the 23rd day as in sheep, buffalo and equine feti at 25th day of gestation (Morini et al, 2016;Rodrigues et al, 2014;Trahair & Robinson, 1986), respectively. The primitive intestine was covered by mesenchymal mass on the 23rd day similarly to equine feti at 25th day of gestation (Franciollia et al, 2011).…”
Section: Histogenesis Of Intestinementioning
confidence: 52%
“…In total, 33 chorioallantoic membranes were collected in slaughterhouse at Macapá, (North of Brazil) from pregnant water buffalos with estimated gestational ages ranging from 30 to 53 days. Estimations of the gestational age were done on the basis of the crown‐rump length following standardized methods (Abdel‐Raouf & El‐Naggar, ) and according to the external features of the embryos and foetuses as previously published by our group (Morini et al, , ), see Table .…”
Section: Methodsmentioning
confidence: 99%
“…For placental tissues, the samples were paired samples from the maternal and fetal parts of the uterine placentome of the same animal. Size of the crown rump length (CRL) of the fetus was used as a reference to calculate the stage of pregnancy (Figure 1; Edward, 1965;Soliman, 1975;Morini et al, 2016). Based on CRL, tissues from the animals of Day 25 and Days 30-35 of pregnancy were collected in cold Dulbecco's phosphate-buffered saline (DPBS) and washed and stored in RNA later (Fajardy et al, 2009;Aliniyaa et al, 2017).…”
Section: Tissue Sample Collectionmentioning
confidence: 99%